2016
DOI: 10.1002/jcp.25329
|View full text |Cite|
|
Sign up to set email alerts
|

Emerging From the Unknown: Structural and Functional Features of Agnoprotein of Polyomaviruses

Abstract: Agnoprotein is an important regulatory protein of polyomaviruses, including JCV, BKV, and SV40. In the absence of its expression, these viruses are unable to sustain their productive life cycle. It is a highly basic phosphoprotein that localizes mostly to the perinuclear area of infected cells, although a small amount of the protein is also found in nucleus. Much has been learned about the structure and function of this important regulatory protein in recent years. It forms highly stable dimers/oligomers in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 114 publications
(202 reference statements)
0
38
0
1
Order By: Relevance
“…PML and non-PML patient brain tissue samples were provided by the National NeuroAIDS Tissue Consortium (NNTC, www.nntc.org). We specifically thank Dr. Susan Morgello (Manhattan HIV Brain Bank) for providing initial PML and Non-PML tissue samples White, M. K., & Safak, M., (2016). In C. S. Reiss (Ed.…”
Section: Discussionmentioning
confidence: 99%
“…PML and non-PML patient brain tissue samples were provided by the National NeuroAIDS Tissue Consortium (NNTC, www.nntc.org). We specifically thank Dr. Susan Morgello (Manhattan HIV Brain Bank) for providing initial PML and Non-PML tissue samples White, M. K., & Safak, M., (2016). In C. S. Reiss (Ed.…”
Section: Discussionmentioning
confidence: 99%
“…They all have a highly basic amino acid composition and share a highly significant sequence homology between them (Khalili et al, ). JCV agnoprotein is the most studied one in details among three agnoproteins with respect to its binding partners, functional and structural properties (Saribas et al, ). In this review, we further described the recent developments in the structural and functional properties of agnoprotein of JCV, BKV, and SV40 in great detail as highlighted in upcoming sections below.…”
Section: Polyomavirus Genome and Its Expressionmentioning
confidence: 99%
“…There is an exception to this trend. That is, two of the human polyomaviruses, JCV and BKV and monkey polyomavirus virus, SV40, encode a small regulatory protein from their late genome called Agnoprotein (Frisque, Bream, & Cannella, 1984;Saribas et al, 2016). However, recent discoveries…”
Section: Expression Of the Late Coding Region Of Polyomavirusesmentioning
confidence: 99%
“…We are also interested in analyzing the potential hydrophobic and hydrophilic domains of agnoprotein utilizing a method established by Kyte and Doolittle [Snider et al, ] (http://web.expasy.org/protscale/) [Gasteiger et al, ] as shown in Figure . This analysis allowed us to identify only one hydrophobic domain in agnoprotein, as previously predicted [Saribas et al, ], spanning residues Arg27 to Cys40 with a maximum peak at position Leu32 which encompasses approximately the second predicted α‐helix (Ser19‐Cys40). This region contains the Leu/Ile/Phe‐rich region of the protein, which is highly conserved in agnoprotein for JCV, SV40, and BKV and involved in formation of an amphipathic‐like α‐helix [Roy et al, ; Saribas et al, , ].…”
Section: Resultsmentioning
confidence: 83%
“…). The hydrophobicity and partial amphipathicity of this helical domain could explain the propensity of agnoprotein to dimerize/oligomerize [Saribas et al, , ; Coric et al, ].…”
Section: Resultsmentioning
confidence: 99%